ASPC Manual of Preventive Cardiology. - Amsterdam, Ezra, MD (Demos Medical Publishing, 2014)
Endorsed by the American Society for Preventive Cardiology, this highly practical resource focuses on the application of current guidelines and practice standards in the clinical management of cardiovascular risk factors. The Manual presents concise descriptions of each major cardiovascular risk factor, and practical, to-the-point discussions of current best practices in clinical management. In addition, the Manual includes chapters on peripheral arterial disease, stroke, smoking, contemporary cardiovascular imaging, heart failure, metabolic syndrome, thrombosis, nutrition, spec.